STUDENTS’ ORAL SKILL IMPROVEMENT AS REVEALED IN LEARNING-BASED PERFORMANCE - Didik Rinan Sumekto (English Review: Journal of English Education, 2014)
Abstract: This classroom-based research investigates how interaction and individual performance by means of classroom learning participation has contributed the undergraduate students’ oral skill improvement. This study observes six speaking course meetings which involves 27 sophomore undergraduate English education. Data collected through classroom activities involving students’ performance analysis, observation and oral test technique. Data analyzed through Carr and Kemmis’ classroom action research model examination in two phases. The findings prove that during the interaction and individual-based performance investigation, some students’ oral skill performance increase in the point level. The improvement gains from .25 to .50 points as shown in the second phase. The average score gained in the first phase is 68.30 and 71.12 in the second phase, which indicate that the average achievement is 9.7%. Overall, out of 27 participants, there are 74% or 20 participants gaining an improvement in speaking course IV, whilst other 7 participants do not increase their oral skill performance.Keywords: Adult and independent learners, individual participation, oral skill achievement